STUDI KARAKTERISTIK CAMPURAN HRS-WC DENGAN AGREGAT DILAPISI PLASTIK TIPIS BEKAS - I Nyoman Arya Thanaya; I Made Agus Ariawan; Anak Agung Istri Mirah Primaswari (JURNAL SPEKTRAN, 2019)
ABSTRACTOne problem of the environment is the increasing amount of plastic waste especially thin plastic bag and other thin plastic packaging, therefore effort is needed to utilize those plastic waste. Within this experiment thin plastic waste was use on the production of road asphalt mixture. The aim of this experiment was: to know the effectivity of the plastic coating onto the aggregate; the properties of the aggregate coated with thin waste plastic; and the Marshall characteristic of HRS-WC. Waste thin plastic waste was manually cut with size: <10mm and 10-20mm. The aggregate was heated, then plastic waste was spreaded, mixed, added with optimum asphalt content (OAC), evenly mixed and compacted 2x75 Marshall blow. Plastic coating was found only effective (observed visually) on the coarse aggregate using wider plastic size 10-20mm. Samples of HRS-WC were made with aggregate coated with plastic at OAC; OAC-0.5%; and OAC-1%. It was obtained that: the OAC was 7.55%. For 100% coating the coarse aggregate the amount of plastic needed was 30gram (8.6% by weight of total aggregate), and 15gram to coat 50%. The difference on Marshall Characteristic without and with added plastic was not significant and difficulties was experienced to meet volumetric properties, nontheles there was increase in Marshall stability. It was found that, the Marshall stability, flow, Marshall Quotient, VIM, VMA, and VFB on OAC with 50% plastic coating on the coarse aggregate, were consecutively: 1017.35 kg; 3.05mm; 333.69 kg/mm; 298.94 kg/mm; 4.288%; and 18.055%. Meanwhile on 100% coating, consecutively: 1075.07 kg; 3.59mm; 298.94 kg/mm; 4.037%; 17.462%; dan 76.90%.